Fresno County Bar Association's 110th Annual Bar Banquet Held At Elks Lodge - Watkins, Howard::::::::: (1982)
?, on guitar, Hal Bolen, Jr. wearing cowboy hat on guitar, Lorraine Bolen singing 5080 E. Kings Canyon Road, Fresno